A Comprehensive Review on Human Health, Promoting the Well-Being of Teaching Professionals - H. Mary Henrietta (Three E Science Institute, 2023)
This article thoroughly examines recent research that sheds light on various aspects of human health, emphasizing the interconnectedness of physical, mental, and social well-being. The study explores significant factors that influence health, including genetics, lifestyle choices, environmental factors, and access to healthcare. It relies on current references to emphasize the current knowledge and ongoing research in these areas. Developing successful interventions and policies to promote optimal well-being requires a comprehensive understanding of these factors. The maintenance of overall health and the enhancement of various aspects of well-being are reliant upon regular engagement in a range of health-promoting activities. These activities include exercise, a well-balanced diet, sufficient rest, stress management, nurturing relationships, and ongoing education. A comprehensive understanding of the complex connections among lifestyle, genetics, social factors, and access to healthcare is essential for developing approaches to improve the health outcomes of diverse populations. Recent advancements in the research highlight the significance of adopting a comprehensive approach to health, in which various elements can interact and influence each other. Individuals can take control of their health by incorporating healthy habits into their daily routines and carefully considering the various factors affecting their well-being. This proactive approach can lead to positive changes that ripple effect on society.